PEMANFAATAN MIKROORGANISME LOKAL UNTUK PENGELOLAAN SAMPAH ORGANIK DI DESA SEKARAN - Edi, Nugroho; Abdullah, Muhammad; Partaya, Partaya (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2017)
The village of Sekaran is one of the villages located close to the UNNES Campus. The cur- rent Village of Sekaran villagers are in addition to the natives, UNNES students who rent houses or boarding in the area, and some are urban, or urban, people who prefer suburban residences. Some of the land in the village of Sekaran has turned into housing and one of the closest housing of the cam- pus is Sekar Gading Housing. Residents in Housing Sekar Gading, especially the mothers belonging to Dasa Wisma are very hungry for various activities based on environmentally friendly. One of the activities they want is how to make organic fertilizer especially from household waste. Therefore, the initial plan of activities originally in the village of Banyuwindu devotees move to the village of Sek- aran, especially in Housing Sekar Gading. The main reason for moving the location because after coordination several times Banyuwindu community difficult to determine the time of activity, while the implementation time of service activities should be as soon as possible. While the choice of loca- tion in Housing Sekar Gading because of the welcome and enthusiasm of people in the housing is very good. Targets to be achieved in this activity is the increasing understanding of the community in Housing Sekar Gading in managing waste independently, the community is able to utilize local mi- croorganisms as an environmentally friendly composting material, and can reduce the dependence on the use of chemical fertilizers. The outcomes of this devotional activity are 1) articles for national seminars or journals, 2) appropriate technology (TTG) of local potential waste-based waste manage- ment. The results achieved in this activity is organic fertilizer products using local microorganisms.